Placental Extract Improves Hippocampal Neuronal Loss and Fear Memory Impairment Resulting From Chronic Restraint Stress in Ovariectomized Mice - Kazuhiro Takuma; Hiroyuki Mizoguchi; Yoko Funatsu; Yuko Kitahara; Daisuke Ibi; Hiroyuki Kamei; Toshio Matsuda; Koji Koike; Masaki Inoue; Taku Nagai; Kiyofumi Yamada (Elsevier, 2012)
We have recently found that combination of ovariectomy (OVX) and chronic restraint stress causes cognitive dysfunction and reduces hippocampal CA3 neurons in female rats and mice and that estrogen replacement and chronic treatment with Ginkgo biloba extract EGb 761 suppress the OVX/stress-induced behavioral and morphological changes. In this study, we examined the effect of placental extract on the memory impairment and neuromorphological change in OVX/stress-subjected mice. Female Slc:ICR strain mice were randomly divided into four groups: vehicle-treated OVX, porcine placental extract (120 and 2160 mg/kg)-treated OVX, and sham-operated control groups. Two weeks after surgical operation, OVX mice underwent restraint stress for 21 days (6 h/day), and all animals were then subjected to a contextual fear conditioning test followed by morphological examination by Nissl staining. Placental extract was orally administered once daily until the behavioral analysis was carried out. Chronic treatment with both doses of placental extract improved the OVX/stress-induced fear memory impairment and Nissl-positive cell loss of the hippocampal CA3 region, although it did not affect the loss of bone mineral density and increase in body weight after OVX. These results have important implications for the neuroprotective and cognition-enhancing effects of placental extract in postmenopausal women. Keywords:: postmenopausal animal model, chronic stress, ovariectomy, cognition, hippocampus